Neutron-19C scattering: Emergence of universal properties in a finite range potential - Shalchi, M. A. [UNESP]; Yamashita, M. T. [UNESP]; Hadizadeh, M. R.; Frederico, T.; Tomio, Lauro [UNESP] (Elsevier, 2017)
The low-energy properties of the elastic s-wave scattering for the n-19C are studied near the critical condition for the occurrence of an excited Efimov state in n–n-18C. It is established to which extent the universal scaling laws, strictly valid in the zero-range limit, survive when finite range potentials are considered. By fixing the two-neutrons separation energy in 20C with available experimental data, it is studied the scaling of the real (δ0R) and imaginary parts of the s-wave phase-shift with the variation of the n-18C binding energy. We obtain some universal characteristics given by the pole-position of kcot⁡(δ0R) and effective-range parameters. By increasing the n-18C binding energy, it was verified that the excited state of 20C goes to a virtual state, resembling the neutron–deuteron behavior in the triton. It is confirmed that the analytical structure of the unitary cut is not affected by the range of the potential or mass asymmetry of the three-body system.
Keywords: Efimov physics; Faddeev equation; Few body; Halo nuclei; Scattering theory